More on Identification in Detailed Wage Decompositions - Gardeazabal, Javier; Ugidos, Arantza (The Review of Economics and Statistics, 2004)
Wage decompositions are often used to decompose wage differentials of two demographic groups into differences in characteristics and differences in returns to those characteristics. The latter part is used as an estimate of the degree of discrimination. A problem with this approach is that the contributions of individual dummy variables to the wage decomposition are not identified. This note proposes a simple solution to the identification problem. The solution is illustrated with an empirical application to Spanish labor market data.